(untitled) (Journal of the College of Basic Education, 2023)
E-Learning is on the cusp of a transformation. For several years, it has been a matter of educational institutions implementing systems and processes for delivering courses online. That was a logical. 1st step. that has largely been accomplished.Today’s e-Learning challenge is considerably greater than just bringing courses online, one with a pay-off that will revolutionize education inHuda Abdul Alle Al-AmweeAl-Mustanseriy UniversityComputer scienceThe E-Learning of Network Environment …...………..Huda Abdul Alle Al-AmweeJ. OF COL. OF B .ED. NO.51 2 / 2007ways that online classes only begin to suggest. That challenge is to break through course-based limitations in order to create true Networked Learning Environments. A Networked Learning Environment in the Internet age applies new technology to a very old concept—that learning is much more than classes and grades. It is about the learning that takes place in a vibrant community of people and resources. The Internet has removed the limits of time and proximity that once restricted this community. In a true Networked Learning Environment, any student, instructor or researcher can access any learning resource at anytime from anyplace. Similar to the Internet, a Networked Learning Environment is really a network of networks—as simple as a lecturer and her class or as complex as a global web of instructors collaborating to develop a brand new curriculum. The power of the Networked Learning Environment today is that it creates unlimited possibilities for students and faculty, far beyond the limitation of books, bricks and mortar. While most institutions are evolving toward the Networked Learning Environment one step at a time, some are taking the leap all at once. This white paper describes the NLE and lays out Blackboard’s vision for providing solutions that will help educational institutions realize their goals.